The impact of strategic planning for electronic services to developing cash bank deposits: An Applied research for a sample of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The bank deposits is fuel banking activity and raw material products for the commercial bank and the basis of its activity and its lifetime So the bank, which seeks to continue the successful development of the volume of cash deposits has translated the work of the bank to meet the needs of different sectors by providing the necessary funding, and from this point of view was the research problem a lack of interest departments of banking services to commercial banks as a means for the development of electronic cash deposits have, and which represents the basis for the supplier commercial bank fund.